An intertemporal CAPM with stochastic volatility - Campbell, John Y.; Giglio, Stefano; Polk, Christopher; Turley, Robert (Journal of Financial Economics, 2018)
This paper studies the pricing of volatility risk using the first-order conditions of a long-term equity investor who is content to hold the aggregate equity market instead of overweighting value stocks and other equity portfolios that are attractive to short-term investors. We show that a conservative long-term investor will avoid such overweights to hedge against two types of deterioration in investment opportunities: declining expected stock returns and increasing volatility. We present novel evidence that low-frequency movements in equity volatility, tied to the default spread, are priced in the cross section of stock returns.